2011
DOI: 10.1074/mcp.m111.012203
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Validation of Serum Protein Changes in Type 1 Diabetes Patients Using High Throughput Two Dimensional Liquid Chromatography-Mass Spectrometry and Immunoassays

Abstract: Type 1 diabetes (T1D) is expected to cause significant changes in the serum proteome; however, few studies have systematically assessed the proteomic profile change associated with the disease. In this study, a semiquantitative spectral counting-based two dimensional liquid chromatography mass spectrometry platform was used to analyze serum samples from T1D patients and controls. In this discovery phase, significant differences were found for 21 serum proteins implicated in inflammation, oxidation, metabolic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
69
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 46 publications
(40 reference statements)
9
69
0
Order By: Relevance
“…Consistent with previous studies in children with overt type 1 diabetes, we found lower levels of APOA4 [19], APOC4 [19], CF3 [17,18], CF4 [17][18][19], clusterin [16,17], kininogen [17] and transthyretin [17] in children with islet autoantibodies. We also found lower levels of CF9 in autoantibodypositive children, while others [19] have reported slightly increased levels.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Consistent with previous studies in children with overt type 1 diabetes, we found lower levels of APOA4 [19], APOC4 [19], CF3 [17,18], CF4 [17][18][19], clusterin [16,17], kininogen [17] and transthyretin [17] in children with islet autoantibodies. We also found lower levels of CF9 in autoantibodypositive children, while others [19] have reported slightly increased levels.…”
Section: Discussionsupporting
confidence: 81%
“…2). Eight of those proteins (represented by 14 peptides) overlapped with findings from previous studies [16][17][18][19] (Table 1). This included four of the 14 peptides that were tested in our study because they had been identified in a previous study [17] (Table 1).…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations